Distinctive Features of Radiation Pulses in the Very First Moment of Lightning Events - Mohd Esa, Mona Riza; Ahmad, Mohd Riduan; Rahman, Mahbubur; Cooray, Vernon (Elsevier, 2014)
This paper investigates the existence of distinctive features between 4 different types of lightning discharges, namely negative cloud to ground discharge (−CG), positive cloud to ground discharge (+CG), cloud discharge (IC) and isolated breakdown discharge (IB). A total of 110 very fine structure waveforms of 44 −CG, 16 +CG, 39 IC, and 11 IB discharges have been selected from a collection of 885 waveforms measured using fast electric field broadband antenna system. The measurements were carried out in Uppsala, Sweden from May to August 2010. We found that there are significant distinctions within the first 1 ms among different types of lightning discharges (−CG, +CG, IC, and IB). For example, the pulses in −CG discharges are more frequent than other discharges; the pulses in +CG discharges have the highest intensity and the IC discharge pulses tend to have shorter duration.